A metabolite‐specific 3D stack‐of‐spiral bSSFP sequence for improved lactate imaging in hyperpolarized [1‐13C]pyruvate studies on a 3T clinical scanner. Issue 3 (21st February 2020) - Tang, Shuyu; Bok, Robert; Qin, Hecong; Reed, Galen; VanCriekinge, Mark; Delos Santos, Romelyn; Overall, William; Santos, Juan; Gordon, Jeremy; Wang, Zhen Jane; Vigneron, Daniel B.; Larson, Peder E. Z.
Abstract : Purpose: The balanced steady‐state free precession sequence has been previously explored to improve the efficient use of nonrecoverable hyperpolarized 13 C magnetization, but suffers from poor spectral selectivity and long acquisition time. The purpose of this study was to develop a novel metabolite‐specific 3D bSSFP ("MS‐3DSSFP") sequence with stack‐of‐spiral readouts for improved lactate imaging in hyperpolarized [ 1- 13 C ]pyruvate studies on a clinical 3T scanner. Methods: Simulations were performed to evaluate the spectral response of the MS‐3DSSFP sequence. Thermal 13 C phantom experiments were performed to validate the MS‐3DSSFP sequence. In vivo hyperpolarized [ 1- 13 C ], pyruvate studies were performed to compare the MS‐3DSSFP sequence with metabolite‐specific gradient echo ("MS‐GRE") sequences for lactate imaging. Results: Simulations, phantom, and in vivo studies demonstrate that the MS‐3DSSFP sequence achieved spectrally selective excitation on lactate while minimally perturbing other metabolites. Compared with MS‐GRE sequences, the MS‐3DSSFP sequence showed approximately a 2.5‐fold SNR improvement for lactate imaging in rat kidneys, prostate tumors in a mouse model, and human kidneys. Conclusions: Improved lactate imaging using the MS‐3DSSFP sequence in hyperpolarized [ 1- 13 C ]pyruvate studies was demonstrated in animals and humans. The MS‐3DSSFP sequence could be applied for other clinical applications such as in the brain or adapted for imaging other metabolites such as pyruvate and bicarbonate.